Novel and Emerging Therapies for Inflammatory Bowel Disease - Al-Bawardy, Badr; Shivashankar, Raina; Proctor, Deborah D. (Frontiers in Pharmacology, 2021)
Inflammatory bowel diseases (IBD) such as ulcerative colitis and Crohn’s disease are chronic, relapsing and remitting disorders of intestinal inflammation with potential systemic manifestations. Despite the availability of current biologics, such as anti-tumor necrosis factor (anti-TNF), anti-integrins, anti-interleukins and small molecules such as tofacitinib, the rates of primary and secondary treatment failure remain high in IBD. This highlights the importance of continued development of new therapeutic targets and modifications of existing ones to improve the treatment response rates and to also improve the safety profile and tolerability of these medications. In this review we will discuss novel treatment target agents including selective Janus kinase (JAK) inhibitors, anti-interleukin (IL) (IL-12/IL-23), leukocyte trafficking/migrating inhibitors (such as sphingosine-1-phosphate receptor modulator) and other small molecules currently in development.